The Exploitation of Women's Body and Sensuality: The Attraction of Newspaper Movie Advertisements in Local Daily Newspapers - Hati, Lila Pelita; Ginting , Lestari Dara Cinta Utami; Malik, Rahman (International Journal Linguistics of Sumatra and Malay, 2022)
Newspaper advertising experienced a significant increase in the 1970s. During that period, three local daily newspapers were established in Medan, namely: Waspada, Sinar Indonesia Baru, and dan Analisa. These newspapers displayed various advertisements in their publications; one of which was the advertisement to promote the film that would be shown in theaters at that time. In promoting films through these advertisements, many producers women as a means of promotion. Women seemed to have their magnet to attract the audience's interest. This journal explains how the women’s representation in the local daily newspaper advertisements in Medan in the 1970s, and how the exploitation of women’s bodies and sexual attractiveness in the advertisements for the promotion of the film was related to global discourse, especially in terms of women's appearance. The four stages of historical methods are applied to conduct the research, namely heuristics, verification, interpretation, and historiography. The results of the research show that advertising producers often showcased pictures of beautiful and sexy women and even displayed vulgar words to attract the audience's interest which didn’t represent the storyline of the film itself.